Penentuan Kadar Zat Gizi Makro Dan Aktivitas Antioksidan Daun Katuk (Breynia androgyna (L) Chakrab & N.P.Balakar) Dengan Perbandingan Metode Pengeringan - Aqmallun Nazli, Anny Sartika Daulay (Journal of Health and Medical Science, 2022)
Katuk plant (Breynia androgyna (L) Chakrab & N.P.Balakar has many benefits in everyday life. Katuk plants contain several chemical compounds, including papaverin alkaloids, proteins, fats, vitamins, minerals, saponins, flavonids and tannins. Some of the chemical compounds found in katuk plants are known to be medicinal. In addition, this katuk leave also have antioxidant activity that can help overcome or neutralize free radicals and prevent body damage from the onset of degenerative diseases. This research was an experimental research. This research phase included the manufacture of ethanol ethanol katuk leave (Breynia androgyna (L) Chakrab & N.P.Balakar using maceration methods, phytochemical screening, determination of carbohydrate levels with luff Scrool method, determination of protein levels carried out by the kdejahl method, and determination of fat levels used gravimetry method. While in determining antioxidant activity it was done by the DPPH method in visible spectrophotometry at a wavelength of 516 nm. The results of the research showed the screening of phytochemicals contained in ethanol extracts of oven drying leaves, sunlight and fans contained chemical compounds of alkaloids, flavonoids, saponins, polyphenols, tannins and steroids / triterpenoids. Determination of carbohydrate, protein and fat levels showed that katuk leaf samples contained more macronutrients in drying with ovens than drying sunlight and fans. While in determining the test of antioxidant activity in oven drying katuk leave, sunlight and fans had a very low IC50 value that was below the range of 151-200 ppm. and in the comparison of vitamin C as a positive control, IC50 obtained which was 33.67 ppm.